(untitled) (African Multidisciplinary Journal of Research, 2025)
The power of digital media in Kenya has been demonstrated in the active social engagement and production of news discourse during the recent Generation-Z (Gen-Z) political activism on X Space. The discourse confirms a growing mass participation in news discourse on digital media taking precedence over legacy media. In the age of disruptive technologies, and the production of social-political discourses, an active, critical and content-producing mass is quickly surpassing traditionally assumed passive audience. In Kenya, amid a digital media frenzy over the Gen-Z protests, citizen journalism overrides legacy journalism, and in some cases, raw footage captured at points of witness is uploaded online without as much censorship. The paper applied qualitative in-depth interviews of eight journalists to assess the Gen-Z political activism and production of discourses on X Space. Theories of disruptive technologies were juxtaposed against the agenda-setting theory to identify the positive effects of digital narratives, including facilitating activism, active youth engagement in news discourse and social change. The study found out that a new form of youth activism has emerged, with the youth fruitfully engaging in X Space discourses, which culminate in actual street protests; Digital storytelling represents a powerful fusion of technology and social consciousness, where the young people project their voices of concern; Citizen journalism has fundamentally altered the dynamics of traditional journalism, reshaping the way news is gathered, reported, and consumed; and that during the protests, mainstream media played catch-up as it struggled to keep up with the many discourses emerging from X Spaces. The study recommends that traditional media aim to fully align with the opportunities presented in disruptive innovative developments; and that the Kenyan media grab the opportunity to re-evaluate their approach to gathering and disseminating news in the modern age for sustainable business and to maintain their important agenda-setting and gatekeeping roles.